Effect of high-pressure homogenization on maize starch-stearic acid and maize starch-stearic acid-whey protein complexes - Han, Kaijie; Wu, Yuewei; Peng, Xiangyuan; Zhou, Binran; Wang, Fang; Liu, Xia (Frontiers in Sustainable Food Systems, 2024)
The maize starch (MS)-stearic acid (SA) and MS-SA-whey protein (WP) complexes were prepared using the high-pressure homogenization (HPH). Results from X-ray diffraction (XRD) showed that MS-SA complexes presented an increase in the long-range molecular order with increasing the homogenization pressure, and MS-SA-WP complexes showed only an increase with increasing the homogenization pressure from 10 to 50 MPa. Results from differential scanning calorimetry (DSC) and Raman spectroscopy showed that the amount of complexes and the short-range order of both MS-SA and MS-SA-WP complexes increased with increasing the homogenization pressure. The addition of WP to MS-SA altered significantly the structure and digestion of complexes. Results revealed that MS-SA-WP complexes have more ordered structure and lower digestion than the corresponding MS-SA complexes. The digestibility of all complexes decreased with increasing the homogenization pressure. There was a significant correlation between the digestibility and structural characteristics of complexes. Complexes with better structural stability have better anti-digestion properties. The obtained results are helpful in understanding the structure and digestibility of complexes prepared by HPH, which is valuable for controlling the quality and nutrition of starchy food.